Space in a Social Movement: A Case Study of Occupy Central in Hong Kong in 2014. Issue 4 (November 2019) - Wang, Xu; Ye, Yu; Chan, Chris King-chi
Few studies have examined the role of space in social movements. The existing studies have primarily emphasized the physical nature of space (e.g., space as distance) and overlooked other attributes of space, such as space as the materialization of power relations and space as lived experience. In this article, we explore the role of space in social movements based on a case study of the Occupy Central in Hong Kong in 2014. During the protest, the organizers occupied and reconfigured the campuses and mobilized the participants both through and in space. We find that the campus space helped stimulate the feelings and emotions of the students and increased their enthusiasm to participate in the demonstration. The participants were then sent from the campuses (mobilization spaces) to the demonstration spaces where they occupied and transformed the urban public spaces into private spaces, thus leading to contention over and of space with the state powers. Our findings reveal that the campus space is an important resource that organizers can use for mobilization. We also find that the special features of a campus, including aggregation, networks, isolation, and homogeneity, can facilitate the formation of social movements. We argue that the three attributes of space interact with one another in facilitating the social movement. Thus, our findings suggest that space acts as not only the vessel of struggle but also a useful tool and a target of struggle.